2020
DOI: 10.3390/nu12030840
|View full text |Cite
|
Sign up to set email alerts
|

Association of Coffee, Decaffeinated Coffee and Caffeine Intake from Coffee with Cognitive Performance in Older Adults: National Health and Nutrition Examination Survey (NHANES) 2011–2014.

Abstract: The aim of this study was to examine the association of coffee, caffeinated coffee, decaffeinated coffee and caffeine intake from coffee with cognitive performance in older adults. we used data from the National Health and Nutrition Examination Survey (NHANES) 2011–2014. Coffee and caffeine intake were obtained through two 24-hour dietary recalls. Cognitive performance was evaluated by the Consortium to Establish a Registry for Alzheimer’s Disease (CERAD) test, Animal Fluency test and Digit Symbol Substitution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
108
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(118 citation statements)
references
References 51 publications
6
108
0
4
Order By: Relevance
“…Another limitation of the experimental studies is that most of them were carried out on male animals (or the animal sex was not stated), whereas human studies indicate that the effect of caffeine on cognition is sex-dependent [ 95 , 200 , 201 ]. For example, caffeine intake was associated with better cognitive performance in older women, but not in men [ 202 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another limitation of the experimental studies is that most of them were carried out on male animals (or the animal sex was not stated), whereas human studies indicate that the effect of caffeine on cognition is sex-dependent [ 95 , 200 , 201 ]. For example, caffeine intake was associated with better cognitive performance in older women, but not in men [ 202 ].…”
Section: Discussionmentioning
confidence: 99%
“…Decaffeinated coffee constituents have been demonstrated to exert potential beneficial effects in neurodegenerative diseases [ 94 ]. However, decaffeinated coffee was not associated with a protective effect on cognitive performance in older people [ 95 ]. The data from the human studies do not allow to conclude on the role of caffeine itself in the modulation of AD risk.…”
Section: Caffeine In Alzheimer’s Diseasementioning
confidence: 99%
“…An intervention study showed that the biomarkers of oxidative damage chosen such as 3-nitrotyrosine were lower in high level consumers of instant coffee compared to those who consumed water, suggesting that the consumption of coffee may protect healthy adults from the oxidative damage [ 163 ]. In a clinical study with a total of 2513 participants aged ≥60 years, Dong et al [ 164 ] found that the prevalence of low cognitive performance decreased with increasing intake of total coffee and caffeinated coffee with a nonlinear, L-shaped dose–response relationship. However, no significant association was found between decaffeinated coffee and cognitive performance.…”
Section: Other Ndds and Healthy Subjectsmentioning
confidence: 99%
“…Caffeine attributes to most cognitive benefits. There are mixed studies depicting the positive association of decaffeinated coffee compared to caffeinated coffee affecting cognitive performance [30]. A recent publication by Dong et al concluded from the National Health and Nutrition Examination Survey (NHANES), which was conducted by Centers for Disease Control and Prevention (CDC), that coffee, caffeinated coffee, and caffeine were associated with cognitive performance while decaffeinated coffee was not [30].…”
Section: Review Bioactive Compounds Of Coffee and Their Propertiesmentioning
confidence: 99%